A Novel of Repulsive Function on Artificial Potential Field for Robot Path Planning - H. H. Triharminto; O. Wahyunggoro; T. B. Adji; A. I. Cahyadi; I. Ardiyanto (International Journal of Electrical and Computer Engineering (IJECE), 2016)
In this paper, the issue of local minima associated with GNRON (Goal Nonreachable with Obstacles Nearby) has been solved on the Artificial Potential Field (APF) for robot path planning. A novel of repulsive potential function is proposed to solve the problem. The consideration of surrounding repulsive forces gives a trigger to escape from the local mi- nima. Addition of signum function on the repulsive force which considers relative distance between the robot and the goal ensures that the goal position is the global optima of the total potential. Simulation conducted to prove that the proposed algorithm can solve GNRON and local minima problem on APF. Scenario of each simulation set in different type of obs- tacle and goal condition. The results show that the proposed method is able to handle local minima and GNRON problem.